Optimisation of Luminescent Solar Concentrators through an Integrated Optical & Electrical Model - Mc Cormack, Sarah; Glenn, Aaron (My University, 2025)
Luminescent and Plasmonic Luminescent Solar Concentrators (LSCs and PLSCs) represent significant advancements in solar energy utilisation. This paper introduces and validates a novel, comprehensive two–stage integrated model for optimising and evaluating the performance of these solar concentrating devices. The first stage, termed ‘Plasmon’ is an optical model that systematically optimises the optical characteristics of LSCs and PLSCs. Initially, the optical processes within LSCs were modelled and validated against laboratory–fabricated devices. This validation process was repeated for PLSC simulations ensuring congruence between the modelled and experimental results. Subsequently, the optical model was used to simulate various dye concentrations within LSCs of dimensions cm of which the optimal outputs were fabricated in the lab and tested in both indoor and outdoor environments. The second stage is a novel electrical model developed to predict and evaluate the outdoor performance of the LSC and PLSC devices. The electrical model incorporates the LSC & PLSC optical parameters & dimensions, as well as the direct and diffuse components of the solar radiation spectrum to simulate the devices electrical performance. The role of the electrical model is to predict key performance metrics of power output and power conversion efficiency, thereby providing a comprehensive evaluation of the devices. Comparative analysis shows that the model demonstrates a high degree of accuracy (). This validated novel comprehensive model emerges as a powerful and versatile tool capable of accurately simulating diverse LSC & PLSC device configurations, dye types, and concentrations across various environmental and seasonal conditions. It offers significant material, time, and cost savings in the research and development of these technologies.
PUBLISHED
Cited by: 0; All Open Access; Hybrid Gold Open Access
Keywords: Optical modelling; Electrical modelling; Model validation; Simulations; Fabrication; Optimisation; Characterisation; Luminescent Solar Concentrators; Plasmonic Luminescent Solar Concentrators; solar energy; Nanoscience & Materials; Environmental engineering; Materials Engineering